Studies on genetic parameters and selection indices in eggplant (Solanum melongena L.) for growth and yield attributes (IASH Indian Journal of Arid Horticulture, 2025)
The present experiment was carried out to assess the genetic variability for 60 genotypes of eggplant/ brinjal for growth and yield attributes. A degree of variation was observed for all the characters. High PCV and GCV were recorded for the plant height (22.29 and 22.13), number of primary branches (24.96 and 23.74), intra cluster distance (30.75 and 29.80), number of fruits per plant (38.76 and 37.76), length of fruits (32.07 and 31.97), girth of fruits (29.41 and 29.33), fruit weight (29.26 and 29.20), short styled flowers (31.64 and 22.51), fruit yield per plant (40.52 and 40.30), shoot infestation by shoot and fruit borer (24.34 and 23.83) and fruit infestation by shoot and fruit borer (24.92 and 24.35). High heritability (>60%) was noticed for all the characters under study except short styled flowers (50.64). High genetic advance as per cent mean was observed for fruit yield per plant (82.58%), number of fruits per plant (75.77%), length of fruit (65.67%), fruit weight (60.01%), girth of fruit (60.25%), intra cluster distance (59.50%), fruit infestation by shoot and fruit borer (49.03%), shoot infestation by shoot and fruit borer (48.06%), number of primary branches per plant (46.51%), plant height (45.24%), short styled flowers (33.01%) and inter cluster distance (24.11%). The estimates of genetic parameters revealed scope for further improvement of fruit yield by selection. Top index values for five genotypes were recorded. The genotype SM 36 (4724.25), SM 2 (4676.91), SM 9 (4471.43), SM14 (4313.06) and SM21 (4255.83) respectively and these best five high yielding genotypes were further selected for hybridization programme.